A personal electronic health record: study protocol of a feasibility study on implementation in a real-world health care setting - Ose, Dominik; Weis, Aline; Pohlmann, Sabrina; Hofmann, Helene; Qreini, Markus; Krisam, Johannes; Uhlmann, Lorenz; Winkler, Eva C.; Salize, Hans Joachim; Szecsenyi, Joachim (JMIR Research Protocols)
The overall objective of the study is to implement and evaluate a PEPA prototype for patients with colorectal cancer who are treated at the National Center for Tumor Diseases in Heidelberg